2000
DOI: 10.1002/(sici)1099-0879(200005)7:2<85::aid-cpp234>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Current issues in the assessment and treatment of sexual offenders

Abstract: The present paper reviews what is currently known about sexual abuse and the treatment of the offenders. Sexual offending is primarily committed by males and as many as 50% of females and 33% of males are sexually victimized in some way during their life. While some of these acts involve minimally intrusive behaviours (e.g. exhibitionists), many involve forced vaginal or anal intercourse and varying degrees of associated physical violence and deliberate humiliation of the victim. The effects on the victim can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 92 publications
1
9
0
2
Order By: Relevance
“…Individuals who score low on measures of the domain of Conscientiousness have a tendency to act without considering the consequences (Costa & McCrae, ). Despite the commonly held belief that sex offenders engage in extensive planning of their offenses, less than half of offenders admit to pre‐offense planning (Marshall & Serran, ), and both incarcerated and non‐incarcerated perpetrators have been found to be more impulsive than non‐perpetrators (Hanson, ; Petty & Dawson, ; Spence et al, ). Additionally, individuals who have low scores on Conscientiousness are less likely to adhere strongly to ethical and moral principles (Costa & McCrae, ).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who score low on measures of the domain of Conscientiousness have a tendency to act without considering the consequences (Costa & McCrae, ). Despite the commonly held belief that sex offenders engage in extensive planning of their offenses, less than half of offenders admit to pre‐offense planning (Marshall & Serran, ), and both incarcerated and non‐incarcerated perpetrators have been found to be more impulsive than non‐perpetrators (Hanson, ; Petty & Dawson, ; Spence et al, ). Additionally, individuals who have low scores on Conscientiousness are less likely to adhere strongly to ethical and moral principles (Costa & McCrae, ).…”
Section: Discussionmentioning
confidence: 99%
“…There is agreement that therapeutic process research in sexual offender treatment is under-utilized and that the number of studies is limited (Marshall et al, 2003; Marshall & Serran, 2000). Furthermore, Ward, Polashek and Beech (2006) identified that the issues around the process of change within sexual offender intervention are unspecified.…”
Section: Discussionmentioning
confidence: 99%
“…En una muestra nacional de adultos varones obtenida en EE.UU, se les preguntó si alguna vez habían acosado a un niño, y el 17% dijo que "sí" (Marshall & Serran, 2000). El "Committee on Sexual Offences" dirigió una encuesta nacional en Canadá, en 1984, e hizo un estudio para determinar la frecuencia con la que un menor es víctima de abuso sexual, y concluyó que la mitad de las mujeres canadienses y un tercio de varones canadienses ha sido sexualmente victimizado, y que el 80% de estos fue víctima de abuso sexual antes de los dieciocho años.…”
Section: Otras Variables Relacionadas Con La Agresión Sexualunclassified